Gene Expression Dynamics of Sugar Metabolism and Accumulation During Fruit Ripening in Camellia drupifera - Xue Sun; Muhammad Zeeshan Ul Haq; Ya Liu; Dongmei Yang; Huageng Yang; Yougen Wu (Plants, 2025)
Camellia drupifera, a valuable woody oil crop, holds significant ecological, economic, and medicinal importance. Its seed maturation involves intricate physiological changes, particularly the interplay between oil biosynthesis and sugar metabolism. This study investigates sugar accumulation and the expression dynamics of sugar metabolism-related unigenes during three key developmental stages of C. drupifera fruit: the nutrient synthesis stage (NS), fat accumulation stage (FA), and maturation stage (MS). The findings reveal distinct differences in sugar content and regulatory mechanisms across the stages. The NS stage emerges as a critical period for sugar metabolism, characterized by peak levels of soluble sugars and fructose alongside a significantly elevated expression of sugar metabolism-related unigenes. The significant correlation between sucrose content and gene expression suggests a crucial role of carbohydrates in fruit maturation. Transcriptomic analysis identified key differentially expressed unigenes (DEGs) in sugar metabolism pathways, which qRT-PCR further validated. These results offer novel insights into the molecular mechanisms regulating sugar metabolism during C. drupifera fruit development. At the same time, it provides a theoretical basis for the genetic improvement and effective utilization of other oil crops, supporting their broader agricultural and industrial applications.